2015
DOI: 10.1002/ca.22653
|View full text |Cite
|
Sign up to set email alerts
|

Charcot‐Marie‐Tooth 1A: A narrative review with clinical and anatomical perspectives

Abstract: Charcot-Marie-Tooth 1A (CMT1A) is regarded as the most common hereditary peripheral neurodegenerative disorder. This narrative review highlights perspectives around the historically well-established and characteristic anatomical manifestations of CMT1A seen in the feet, legs and hands, in addition to a clinical diagnosis that may be confirmed by electrophysiology, genetic or molecular markers together with the presence of a typical family history. A less well-known perspective is the potential for systemic man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In vitro studies have demonstrated that NECL4 is needed for myelination (8,10), and the delay in the onset of myelination observed in the in vivo NECL4 Ϫ/Ϫ mouse supports that finding (9). Most dramatic are the morphological abnormalities observed at 2 months of age, in particular focal hypermyelination with tomacula and myelin outfoldings that are characteristic of Charcot-Marie-Tooth neuropathies (9,50). In this study, we describe the complexing of NECL4 with CTL1 and the impact of NECL4 deficiency on choline-dependent metabolism in purified Schwann cells.…”
Section: Discussionmentioning
confidence: 66%
“…In vitro studies have demonstrated that NECL4 is needed for myelination (8,10), and the delay in the onset of myelination observed in the in vivo NECL4 Ϫ/Ϫ mouse supports that finding (9). Most dramatic are the morphological abnormalities observed at 2 months of age, in particular focal hypermyelination with tomacula and myelin outfoldings that are characteristic of Charcot-Marie-Tooth neuropathies (9,50). In this study, we describe the complexing of NECL4 with CTL1 and the impact of NECL4 deficiency on choline-dependent metabolism in purified Schwann cells.…”
Section: Discussionmentioning
confidence: 66%
“…CMT1A is caused by duplication of the peripheral myelin protein 22 ( PMP22 ) gene accounting for more than half of all the CMT cases. The disease usually occurs in the second and third decades [ 2 ], with slowly progressive length-dependent neuropathy [ 3 , 4 ]. Dejerine-Sottas syndrome [ 5 , 6 ], or onset in the late adulthood, has been described occasionally.…”
Section: Introductionmentioning
confidence: 99%